Effects of Physical Activity, Exercise and Sport on Executive Function in Adults Diagnosed with Attention Deficit Hyperactivity Disorder: A Systematic Review - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The main characteristics of attention deficit hyperactivity disorder (ADHD) are associated with inattention, impulsivity, and/or hyperactivity. Those diagnosed with this neurodevelopmental disorder present with executive function and motor difficulties, which have repercussions in educational, occupational, or social areas. On the other hand, it has been evidenced that the regular practice of physical activity or exercise or sport could produce improvements in areas with difficulties. It is for this reason that the objective of the present review was to describe and analyze the effects of the practice of physical activity, exercise, or sport on executive functions in adults diagnosed with ADHD through the scientific literature (registry: INPLASY202530105). The articles indexed in PubMed (1145), Scopus (43), and WoS (2910) were searched using the following keywords: “Adult” OR “Adults” AND “Attention-Deficit/Hyperactivity Disorder” OR “Attention-Deficit with Hyperactivity Disorder” AND “Physical activity” OR “Exercise” OR “Sports” OR “Sport” AND “Executive Function”. In addition, four articles were identified using other search engines. A total of 10 articles met the selection criteria. TESTEX was used to assess the quality of the articles, and TIDierR was used to report the results. Of the ten included studies, nine mention an improvement in inhibitory control, six in selective attention, three in cognitive flexibility, and one in working memory (all p < 0.05). It was concluded that the practice of physical activity, exercise, or sport has a positive and significant effect on the executive functions of adults with ADHD, specifically on selective attention, inhibitory control, and cognitive flexibility. Furthermore, benefits were observed in depression, brain activation, and stability. Among the limitations is the lack of a meta-analysis, which makes it difficult to quantify and recommend which intervention is most effective for this population. Furthermore, the various types and degrees of ADHD were not considered. © 2025 by the authors.